Possessive Adjectives Formed from Personal Names in Polish Translations of the New Testament - Zarębski, Rafał (Studia Ceranea, 2013)
The study focused on possessive adjectives derived by means of the suffixes -ow(y), -in, -sk- formed from proper personal names in old and contemporary translations of the New Testament. Adjectival derivatives have been excerpted from 15 full and 6 incomplete translations of the New Testament, which date back to the 16th, 17th and 20th century. These translations differ in methods of translation (loose and word-for-word; philological, interlinear, ecumenical, dynamic and artistic) and its basis (Greek original or Latin Vulgate). The comparative analysis of old and contemporary translations shows that possessive adjectives, though used frequently in former times, are now going out of use and the substantival genitival attribute is taking their place. This phenomenon is reflected in processes linked with the development of the Polish language. Moreover, tracking the use of the type of adjectives analysed can be used to distinguish various methods of translation. The use of possessive adjectives in contemporary texts suggests respect for the tradition of translation, whereas the failure to use them – the modernization of Polish.